Purification of a proteolytic enzyme from the venom os Bothrops brazili sanke and estudy of its activity on fibrinogen - Azañero, María (2000)
A proteolitic enzyme was purified from Bothrops brazili peruvian snake venom using Sephadex G-100 followed by CM-Sephadex C-50, in both two cases with 0.05M ammonium acetate pH 7,0. The enzyme was purified 3,2 fold with 52,5% of yield and by gel filtration the enzyme showed 18 000 of molecular weight, while the PAGE-SIDS showed only one protein band of 22 000 in the presence of mercaptoethanol and 20 300 under nonreducing conditions which suggests that the enzyme has a single polypeptide chain with disulfide bond. The enzyme hydrolizes fibrinogen, fibrin, casein and albumin, but not hemoglobin and mioglobin. The enzyme is a Aa-fibrinogenase because preferentially hydrolizes the Aa chain of the fibrinogen molecule. This activity is inhibited by EDTA but not by PMSF, TLCK, iodoacetate and pepstatin, suggests that is a metalloproteinase, however the ions Ca++, Mg++ and Zn++ cannot reactivate the inhibition by EDTA. Finally the enzyme is stable up to 45 °C and in its effect on fibrin the enzyme is to attack a chain rapidly.